The beekeeper : pollinating your organization for transformative growth - Desiderio, Katie P.; Frino, Michael G. (Ascent Audio, 2023)
Become a beekeeper and grow your business Catherine had just celebrated her forty-third birthday on May 20th. Her dream of owning and running a thriving company was coming true. Essentially Proximal's essential oil line was becoming a major success, and her company was in growth mode. As a female business owner, she was doing her best to promote positive culture at work and retain talent. Her goal was to build a diverse high-performing and inclusive leadership team, but her leadership team was struggling to put people first and live the mission and values of the company. She had to make some serious changes to ensure the future success of the company. She decided to take some time over the summer to recharge with her family. When the family arrived at H. Ives Family Farms, Catherine quickly realized that the farm was much more than just a family vacation. It was where she learned to become The Beekeeper, enabling her to transform the culture at Essentially Proximal. The story brings to life the world of a Beekeeper and how understanding bees' role in the growth of all things around us has transferable knowledge for anyone wanting to effectively lead. Families, organizations, and farms need more Beekeepers, and this book is the catalyst to becoming one.